Highly Nonlinear Chalcogenide Glass Waveguides for All-optical Signal Processing - Luther-Davies, Barry (2017)
I describe the development of highly nonlinear chalcogenide glass waveguides for photonics and their application as nonlinear optical devices for high speed processing and monitoring of telecommunications signals.